Abrogation of Rb Tumor Suppression Initiates GBM in Differentiated Astrocytes by Driving a Progenitor Cell Program - Adhikari, Amit S.; Sullivan, Teresa; Bargaje, Rhishikesh; Lu, Lucy; O’Sullivan, T Norene; Song, Yurong; Van Dyke, Terry (Frontiers in Oncology, 2022)
Glioblastoma (GBM) remains lethal with no effective treatments. Despite the comprehensive identification of commonly perturbed molecular pathways, little is known about disease etiology, particularly in early stages. Several studies indicate that GBM is initiated in neural progenitor and/or stem cells. Here, we report that differentiated astrocytes are susceptible to GBM development when initiated by perturbation of the RB pathway, which induces a progenitor phenotype. In vitro and in vivo inactivation of Rb tumor suppression (TS) induces cortical astrocytes to proliferate rapidly, express progenitor markers, repress differentiation markers, and form self-renewing neurospheres that are susceptible to multi-lineage differentiation. This phenotype is sufficient to cause grade II astrocytomas which stochastically progress to GBM. Together with previous findings, these results demonstrate that cell susceptibility to GBM depends on the initiating driver.